OPTIMIZATION OF CULTURE CONDITIONS FOR BAKER’S YEAST CELL MASS PRODUCTION- A PRELIMINARY STUDY - Inparuban, K.; Balakumar, S.; Vasantharuba, S.; Arasaratnam, V. (My University, 2009)
The aim of this study was to find out suitable culture conditions to improve the cell mass production of Saccharomyces cerevisiae. S.cerevisiae was grown in a medium(300C, pH 5.0) with sucrose (Table sugar) from 10 to 50 g/L-1 along with (g/L-1) yeast extract (2.5), bacteriological peptone(1.15), NH4HPO4(0.25) and MgSO4.7H2O(0.025). Highest cell mass of 4.43 g/L-1 was obtained in the medium with 50 g/L-1 of sucrose. When the oxygen supply and diffusion were improved by either, mixing in a shaker (100rpm), by an impellor (100 rpm) or aeration (100 bubbles/min), highest cell mass (4.52 g/L-1) was obtained with aeration. Increase in aeration rate to 200bubbles/min increased the yeast cell mass to 5.41 g/L-1. For volumetric scaling up, medium to flask volume ratio was maintained as 1:2, in 1,2,3 and 5 L flasks, and the highest cell mass (5.53 g/L-1) was produced in 2L flask. By optimizing the culture conditions the yeast cell mass production was increased by 1.25 times
Keywords: Baker’s yeast; Cell mass production; Aeration; Reaction volume ratio